Using Visual Dictionary to Improve Vocabulary of the Students - Ramdania, Siti Rahma; Marhum, Mochtar; Wahyudin, Wahyudin (Yayasan Kyadiren, 2025)
This study aims to evaluate the effectiveness of using a visual dictionary to enhance vocabulary mastery among seventh-grade students at SMP Negeri 15 Palu. A pre-experimental research design was employed, involving a single experimental group consisting of 21 students. Data were collected using a pre-test and post-test administered before and after the treatment. The intervention, which involved the use of a visual dictionary as a learning tool, was applied exclusively to the experimental group. The results of the analysis revealed a notable improvement in students’ vocabulary performance. The average score increased from 66.66 on the pre-test to 78.1 on the post-test. Furthermore, statistical analysis indicated that the calculated t-value (51.25) exceeded the critical t-table value (281.21), confirming that the difference between the scores was statistically significant. These findings provide empirical evidence that the use of a visual dictionary is effective in improving vocabulary mastery among The seventh-grade students .